FAKTOR-FAKTOR YANG BERHUBUNGAN DENGAN KEJADIAN RUPTURE PERINEUM PADA IBU BERSALIN NORMAL - Prafita Sari; Amlah Amlah; Eka Rahmawati (PREPOTIF : JURNAL KESEHATAN MASYARAKAT, 2022)
A tear in the birth canal is trauma caused by the birth of a baby that occurs in the cervix, vagina or perineum. The tears that occur can be minor (blisters, lacerations), episiotomy wounds, spontaneous perineal tears from mild degrees to total detail rupture (disconnected anal sphincter), tears in the vaginal wall, uterine fornix, cervix, area around the clitoris and urethra, even the most severe such as rupture. uterus. Based on the Indonesian Demographic Health Survey (IDHS) in 2012, the MMR in Indonesia is still quite high, at 248 per 100,000 live births, this figure is still the highest in Asia, while the target for the National Medium Term Development Plan (RPJMN) is 226 per 100,000 live births. The biggest causes of maternal death that occur during the puerperium are bleeding 28%, eclampsia 24%, infection 11%, and others at 11%. The purpose of this study was to determine the relationship between primiparas, maternal birth spacing and birth weight simultaneously with the occurrence of perineal rupture in normal delivery mothers in the Semuntul Health Center area, Banyuasin Regency in 2020. This study was quantitative using an analytical survey method with a cross sectional approach. The cross sectional research design is a study in which all the variables, both dependent variable (perineal rupture) and independent (primipara, birth spacing and birth weight). P Value = 0.000, birth weight variable obtained P Value = 0.000 <0.05 this indicates that there is a significant relationship between primiparas, gestational interval and birth weight with the incidence of perineal rupture.   Keywords         : Birth Weight, Pregnancy Distance, Primipara, Perennial Rupture